PERKAWINAN DI BAWAH TANGAN MENURUT HUKUM ISLAM DAN PENGARUHNYA TERHADAP ANAK - Ismail H. Tomu (JURNAL LEGALITAS, 2010)
Marriage is a matter of religion than also including the state issues, religious issues as it relates to its implementation shall be in accidance with the terms and provisions of the religious foundation that qualifies as a legitimate religious service, referred to as problem countries because if problems assosiated with administrative control of the state regarding the listing of the marriages in Indonesia. Marriage under the hand, brings unexpected consequences for women and children born of such matiages, especially in the review of the judical aspect, there is no legal protection for both live and earn recognition status. The Indonesian government has signed the Convention On The Elimination Of all Forms Of Discrimination Againts woman atau Cedaw, Keywords: Marriage is Not Valid, Islamic Low, Effect, Children